2019
DOI: 10.1186/s13104-019-4408-8
|View full text |Cite
|
Sign up to set email alerts
|

Low dietary diversity and its influencing factors among a San group in Namibia

Abstract: Objective Although the San in Namibia have been targeted by intensive development efforts, there is little knowledge available about San diet quality and nutritional status. The objective of this study is therefore to estimate and quantify the dietary diversity of a San group, and to investigate how socioeconomic characteristics affect dietary diversity. The dietary data (n = 200) for this cross-sectional study were collected as a part of a larger doctoral research investigating food environment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
11
2
Order By: Relevance
“…The finding of our study was higher than the pooled prevalence of DHS data of 32 sub-Saharan African countries yielding 15.9% [46]; 28.1% in Malawi and in Tanzania the prevalence of overweight and obesity among adults were 24.1% and 19.2% [47]. In study conducted in Namibia among a San groups show 87.5% of the participants consumed food items from only 2 or 3 different food groups, the most frequently eaten food type being maize meal [31]. Similarly, in Addis Ababa reported that 60.4% of them had low DDS [32], 39.7% of people ≥ 40 years had non-diversified diet in Jimma town [33] and in Mirab Abaya wereda Southern Ethiopia had low ( 65.7%) and 34.3% high DDS [34].…”
Section: Magnitude Of Central Obesitycontrasting
confidence: 62%
“…The finding of our study was higher than the pooled prevalence of DHS data of 32 sub-Saharan African countries yielding 15.9% [46]; 28.1% in Malawi and in Tanzania the prevalence of overweight and obesity among adults were 24.1% and 19.2% [47]. In study conducted in Namibia among a San groups show 87.5% of the participants consumed food items from only 2 or 3 different food groups, the most frequently eaten food type being maize meal [31]. Similarly, in Addis Ababa reported that 60.4% of them had low DDS [32], 39.7% of people ≥ 40 years had non-diversified diet in Jimma town [33] and in Mirab Abaya wereda Southern Ethiopia had low ( 65.7%) and 34.3% high DDS [34].…”
Section: Magnitude Of Central Obesitycontrasting
confidence: 62%
“…Our systematic review of the literature (S1 Text, S1 Fig, and S3 Table ) found that most previous studies on drivers of food consumption in SSA focused on fruit and vegetable intake [21,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. We did not find many significant predictors of fruit intake in our study, but in the rainy season, food affordability, particularly indicators of higher wealth, predicted higher fruit intake in both mothers and children.…”
Section: Plos Onecontrasting
confidence: 50%
“…Dietary diversity provides information on household access to a variety of foods [ 67 ], and the Household Dietary Diversity Score (HDDS) is intended to reflect a household’s economic ability to access a variety of foods [ 32 ]. In other studies, relationships between the HDDS and the socioeconomic characteristics of the households have been captured, including age, sex, level of education of the head of household, employment status or income, food expenditure, size of agricultural land, training received regarding food preparation and human nutrition, among others [ 9 , 55 , 68 , 69 ]. It is clear that the crisis generated by the COVID-19 pandemic is having and will continue to have consequences on household diets.…”
Section: Discussionmentioning
confidence: 99%
“…The results also show that the level of education of the head of the household contributes to the improvement of the HDDS. Several studies have shown a positive association between level of education and dietary diversity [ 5 , 9 , 42 , 68 , 72 ]. This means that education has an impact on household nutritional knowledge and the skills to conceptualize and use messages promoting nutrition, consequently contributing to greater dietary diversity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%